Draft Genome Assemblies of Two Staphylococcus pseudintermedius Strains Isolated from Canine Skin Biopsy Specimens - Cao, Wenqi (Microbiol Resour Announc, 2020)
Staphylococcus pseudintermedius is a Gram-positive bacterial species highly relevant to animal and human health. In this study, we report the draft genome sequences of two clinical isolates of S. pseudintermedius from canine skin biopsy specimens at the Dermatology Service of the Auburn University Small Animal Teaching Hospital.